1992
DOI: 10.1177/0093854892019003003
|View full text |Cite
|
Sign up to set email alerts
|

Women in Small-Town Policing

Abstract: This study examined the relationships among job performance, Minnesota Multiphasic Personality Inventory scores, self-perceived stress, and supervisory-perceived stress for female police officers. Thirty full-time female officers from 19 small-town departments served as subjects, representing 91% of all full-time female municipal officers in Vermont. A comparable group of 30 full-time male officers from the same departments and matched for experience was used as a control group. Results showed that, to a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For example, Kurtz (2008) reported stress was significantly associated to making violent arrests for female officers but not male officers, while association to a victim or offender was a significant stressor for men but not for female officers. Furthermore, Bartal et al (1992) reported female officers experienced significantly more stress than their male colleagues when faced with incidents relating to tragedy or danger.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Kurtz (2008) reported stress was significantly associated to making violent arrests for female officers but not male officers, while association to a victim or offender was a significant stressor for men but not for female officers. Furthermore, Bartal et al (1992) reported female officers experienced significantly more stress than their male colleagues when faced with incidents relating to tragedy or danger.…”
Section: Introductionmentioning
confidence: 98%
“…This is consistent with the findings of Violanti et al (2016) that female officers reported a higher rate of stress than males to events involving tragedy or danger. Also, Bartol et al (1992) found in their study that the stressors experienced were the same in the male and female officers except for those stressors related to police operation, where the women reported more stress in facing tragedy and the occasions associated with a responsibility for the safety of the citizens and their colleagues. This finding is in line with our results on higher stress in relation to significant others in female police officers.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, Bartol et al (1992) argue that although the sources of stress are basically the same for men and women, the latter are more vulnerable to stressors linked to tragedies, safety of the public and their professional colleagues. However, He et al (2002) study indicates that women have better coping mechanisms for depression.…”
Section: Demands Of the Post: Physical Competence And Soft Skillsmentioning
confidence: 99%